Sosialisasi Penerapan Model Senam Fun Young Pada Pembelajaran Penjas - Parengkuan, Meyke; Mile, Rifky (Universitas Negeri Gorontalo, 2025)
This community service activity aims to socialize the implementation of the Fun Young Gymnastics model as an alternative in Physical Education learning that is enjoyable and capable of increasing students’ learning motivation at the junior high school level. The activity was carried out at SMP Negeri 2 Limboto on July 11–12, 2025, involving 5 teachers and 60 seventh-grade students. The implementation method included material presentation, demonstration, and hands-on practice by participants. Evaluation was conducted through observation, questionnaires, and activity documentation. The results showed that teachers demonstrated high understanding of the material and enthusiasm to apply it in class. Students showed active engagement, positive expressions, and improved learning motivation. Questionnaire results also revealed very positive responses from both teachers and students regarding the Fun Young model. This activity confirms that a rhythmic and enjoyable movement-based approach can serve as an effective and contextual innovation in Physical Education learning. This program also produced a guidebook and practice video as sustainable outputs for future use by teachers.